Transcending the Shadow of Alcoholism. (3rd January 2022) - Tyler, Susan
Abstract : This paper explores potential reasons why a high proportion of children of alcoholics develop significant substance misuse problems. The author suggests it is potentially indicative of transgenerational trauma, which results in developmental deficits that may be managed by substance misuse. The paper describes how Jung's concept of the transcendent function provides a powerful therapeutic tool to link divided and split off parts of the self in a containing matrix. This is contrasted with Kleinian approaches to addictive states of mind. The alcoholic defence or 'solution' is examined through a Jungian lens. The transformative potential lies in holding the tension between wanting to 'give up' the family cycle of alcoholism versus 'giving in' to the alcoholic solution. Moving away from an identification with the alcoholic solution involves mourning and loss which is often vehemently resisted. The value in Jung's idea of the transcendent function is in the creative potential leading to growth arising from the dynamic tension of these opposites. The paper describes how they come together in fantasy, symbols and transference using a clinical case.